Risk and returns of sustainable crop intensification: The case of small-holder rice and potato farmers in Uganda - Van Campenhout, Bjorn; Bizimungu, Emmanuel (John Wiley & Sons, 2018)
The use of modern inputs such as synthetic fertilizers is often put forward as the best way to increase crop yields in an ecologically sustainable way. However, such inputs can be perceived as risky, and adoption may depend on how much extra risk a farm household can afford. This article describes the potential for fertilizer and pesticide use among Ugandan smallholder rice and potato farmers. In addition, it documents patterns observed in socioeconomic data that suggest that risk is an important barrier to sustainable crop intensification practices. We find that households that engage in risk-management strategies, such as investing in risk-reducing technology or engaging in precautionary savings, are more likely to practise intensified cropping. We also elaborate on the policy consequences.